1999
DOI: 10.1097/00005537-199906000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Double cartilage block ossiculoplasty in chronic ear surgery

Abstract: The DCB represents an excellent alternative to biocompatible prostheses for ossicular reconstruction in the setting of severe chronic ear disease. As with all methods of ossiculoplasty, long-term follow-up will be necessary to determine if this technique remains stable in the hostile environment in which it has been employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
4
5
0
Order By: Relevance
“…Reilly at the same time had achieved a mean A-B gap of 18.6 dB with the same material [11]. Harvey reported that by using pre-sculpted homograft septal cartilage in type III tympanoplasty he could achieve a mean post operative A-B gap of 23.8 dB [12]. Our study had achieved a mean post operative A-B gap of 18.03 dB which is comparable to the above cited studies.…”
Section: Discussionsupporting
confidence: 86%
“…Reilly at the same time had achieved a mean A-B gap of 18.6 dB with the same material [11]. Harvey reported that by using pre-sculpted homograft septal cartilage in type III tympanoplasty he could achieve a mean post operative A-B gap of 23.8 dB [12]. Our study had achieved a mean post operative A-B gap of 18.03 dB which is comparable to the above cited studies.…”
Section: Discussionsupporting
confidence: 86%
“…7 There was significant hearing improvement from preoperative air bone gap of 39.8±7.7dB to 22.18±7.9dB after 6 months of septal cartilage tympanoplasty type 3. Our results are comparable to Harvey et al 8 which reported a similar improvement in mean air bone gap of 23.8dB after double cartilage tympanoplasty. Eleftherios A et al 1 also reported the mean air bone gap reducing from 40dB to 19dB in 6 months, follow up after type 3 chondrotympanoplasty.…”
Section: Discussionsupporting
confidence: 90%
“…Harvey and Lin reported, on 20 cases of original DCB ossicular reconstruction, successful hearing results in 50% of cases (8). They relate their results to the incidence and the severity of active disease in the series.…”
Section: Discussionmentioning
confidence: 99%